EP1271 Prognostic implications of histological tumor regression (Böhm´s score) in patients receiving neoadjuvant chemotherapy for high grade serous tubal & ovarian carcinoma. (1st November 2019) - Rajkumar, S; Polson, A; Nath, R; Lane, G; Sayasneh, A; Tranoulis, A; Jakes, A; Begum, S; Mehra, G
Abstract : Introduction/Background: Primary objective of this study was to determine prognostic significance of Bohm´s histopathological regression score in patients who received neoadjuvant chemotherapy (NACT) for treatment of high grade serous (HGS) tubal & ovarian carcinoma. Methodology: This was a retrospective cohort study of patients who received NACT between 2010 and 2015. The 3 point histopathological regression score of Böhm was used to classify chemotherapy response. Survival outcomes between the 3 different subgroups was analysed and compared with standard clinico-pathological variables using the Cox proportional hazards model and log-rank test. Results: Study cohort comprised 111 patients. Chemotherapy response score (CRS) 3 was observed in 47 (42.4%) and CRS 1and CRS 2 in 22 (19.8%) and 42 (37.8%) women respectively. Women with CRS score of 1 and 2 combined showed a three-fold increased risk of progression on both univariate and multivariate assessment (HR 3.54; C.I 2.19–5.72, p < 0.001). The median overall survival for patients with CRS 1 was 34 months, CRS 2 was 30 months and 47 months for CRS 3. CRS 1 and 2 combined was the only variable that held significance in prediction of reduced overall survival on multivariate assessment (HR 3.26, C.I 1.91–5.54, p 0.0006). CRS 1 and 2 were also associated with 5.15-fold increased risk of relapse within 6 months of completion of chemotherapy (Odds ratio OR 5.15, C.I 0.07–0.47, p - 0.002). Conclusion: CRS is an independent prognosticator of survival and reliable predictor of relapse within 6 months in advanced high grade serous tubal and ovarian carcinoma patients receiving NACT. Disclosure: Nothing to disclose